"x^3 p^2 +x^2 yp+a^3=0" ---(1) is the given differential equation, where "p=dy\/dx"
"\\implies y=-xp-a^3\/(x^2p)"
Differentiating with respect to x, we get;
"p=-p-xdp\/dx+a^3\/x^2p^2(dp\/dx)+2a^3\/x^3p"
"\\implies 2p+xdp\/dx=2a^3\/px^3+a^3\/x^3p^2(dp\/dx)"
"\\implies 2p(1-a^3\/x^3p^2)+xdp\/dx(1-a^3\/x^3p^2)=0"
"\\implies 2p+xdp\/dx=0"
"\\implies\\int dp\/p=-2\\int dx\/x"
"\\implies px^2=c \\implies p=c\/x^2" ---(2)
Substituting (2) in (1), we get;
"c^2+xyc+a^3x=0" which is a quadratic equation in c;
Equating it's discriminant to 0, we get;
"x^2y^2-4a^3x=0"
"\\implies x(xy^2-4a^3)=0"
"\\implies x=0 andxy^2-4a^3=0"
Both these satisfy (1).
Thus, "x=0" and "xy^2-4a^3=0" are the singular solutions of the given differential equation.
Comments
Leave a comment